Distribution and environmental preferences of deep sea benthic foraminifera in the panama basin, eastern pacific ocean (2013)
The Recent benthic foraminiferal families Bolivinidae, Buliminidae and Uvigerinidae from 34 core top samples were studied in order to analyze their geographic distribution and possible environmental controls in the Panama Basin. A cluster analysis defined five assemblages based on the percentage abundance of 33 species. The Bolivinidae and Buliminidae have a homogeneous distribution along the basin, in comparison to the Uvigerinidae, which has its largest proportion over the western flank of the Cocos Ridge and over the north-western flank of the Carnegie Ridge. A canonical correspondence analysis (CCA) over 26 species suggests that the Bolivinidae and Buliminidae are related to bottom temperature, in comparison to the Uvigerinidae, which has a more complex relation with depth, salinity and dissolved O2 content.